2011
DOI: 10.1007/s10566-011-9146-6
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Attachment Relationships: A Study of Adolescents in Wilderness Treatment

Abstract: This study examined shifts in adolescents' attachment relationships with parents and peers during a 7-week wilderness therapy program. Ninety-six adolescents, aged 14-17, completed three quantitative measurements evaluating attachment relationships with mother, father and peers pre and post treatment. Adolescents reported improved attachment relationships in terms of decreased anger and increased emotional connection towards parents. Results also showed adolescents' more troubled attachment relationships in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
0
36
0
2
Order By: Relevance
“…In fact, previous research on OBH has found it to negatively impact the youth -parent attachment, even though youth reported significant mental health improvements post OBH participation (Bettmann & Tucker, 2011). In Bettmann and Tucker's study (2011) OBH youth perceived their mothers and fathers to be significantly less sensitive and responsive to their emotional states and youth were less trusting by the end of treatment that parents would understand their needs and desires (Bettmann & Tucker, 2011). In our study, we did not compare transported and non-transported youth; however, this too may add to the level of disconnect youth may feel from their parents.…”
Section: Jtsp • 35mentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, previous research on OBH has found it to negatively impact the youth -parent attachment, even though youth reported significant mental health improvements post OBH participation (Bettmann & Tucker, 2011). In Bettmann and Tucker's study (2011) OBH youth perceived their mothers and fathers to be significantly less sensitive and responsive to their emotional states and youth were less trusting by the end of treatment that parents would understand their needs and desires (Bettmann & Tucker, 2011). In our study, we did not compare transported and non-transported youth; however, this too may add to the level of disconnect youth may feel from their parents.…”
Section: Jtsp • 35mentioning
confidence: 92%
“…Given that length of treatment is not a predictor of FAD improvement per mothers' and fathers' reports, one possible explanation for this might be that a longer period of time apart from parents could leave youth feeling disconnected from their parent(s), particularly after going through such an intensive experience as an OBH program. In fact, previous research on OBH has found it to negatively impact the youth -parent attachment, even though youth reported significant mental health improvements post OBH participation (Bettmann & Tucker, 2011). In Bettmann and Tucker's study (2011) OBH youth perceived their mothers and fathers to be significantly less sensitive and responsive to their emotional states and youth were less trusting by the end of treatment that parents would understand their needs and desires (Bettmann & Tucker, 2011).…”
Section: Jtsp • 35mentioning
confidence: 93%
“…Continuous trekking or expedition model uses continuous hiking, camping, and backpacking in groups on a wilderness route (Vissell 2004). This model is typically used in short term programs with maximum length of stay of 60 days (Bettmann and Tucker 2011). Short term residential WT programs are designed to last until the adolescent has made significant progress, but typically range from six to 12 weeks (Hagan 2002).…”
Section: What Are Wilderness Therapy Programs?mentioning
confidence: 99%
“…From Prochaska and DiClemente's (1983) writing, one can infer that wilderness therapy will be less effective in supporting growth in the later stages of change that are dependent upon time and proximity to triggering situations, such as unhealthy family dynamics, substances, or unsupportive peer environments. And while there is tremendous benefit to adolescents being separated from their parents during a wilderness therapy program (Bettmann and Tucker 2011;Harper and Russell 2008), families do not have the opportunity to practice new skills together daily. Taylor (2004) highlights the ethical importance of treating clients within the least-restrictive environment.…”
Section: Strengths and Limitations Of Wilderness Therapymentioning
confidence: 99%
“…Taylor (2004) highlights the ethical importance of treating clients within the least-restrictive environment. Perhaps counterintuitive, many parents who choose to send their adolescent child to a residential therapeutic program, at times thousands of miles from home, are providing the least restrictive setting to support change and growth (Bettmann and Tucker 2011;Russell 2005). Parents often express believing that removing their child from the unhealthy environment was the only way to gain the clarity necessary to create change (Harper and Russell 2008).…”
Section: Strengths and Limitations Of Wilderness Therapymentioning
confidence: 99%